SIMULTANEOUS SACCHARIFICATION AND CO-FERMENTATION (SSCF) FOR BIOETHANOL PRODUCTION FROM BAMBOO SHOOTS: A SYSTEMATIC LITERATURE REVIEW - Nasution, Nurul Cinthiya; Machfud; Syamsu, Khaswar (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
The escalating global energy demand and the depletion of fossil fuel reserves have accelerated the pursuit of sustainable bioenergy alternatives. Bioethanol is widely recognized as a promising candidate; however, its production continues to depend predominantly on food-based substrates such as cassava and molasses, thereby exacerbating food vs fuel dilemmas. Consequently, lignocellulosic biomass has emerged as a viable alternative owing to its abundance and non-food nature. Among potential resources, bamboo shoots constitute a particularly strategic feedstock, characterized by high cellulose (33–45%) and hemicellulose (23–30%) contents, coupled with an exceptionally low lignin fraction (0.89%), which minimizes the requirement for energy- and cost-intensive pretreatment. Their rapid growth further reinforces their suitability as a renewable and underexploited biomass source. The present study undertakes a systematic literature review to assess the potential of bamboo shoots for bioethanol production via Simultaneous Saccharification and Co-Fermentation (SSCF). Specifically, it seeks to: (i) elucidate global research trends in SSCF through bibliometric analysis, (ii) identify knowledge gaps concerning the utilization of bamboo shoots, and (iii) propose future research directions to enhance SSCF efficiency. Bibliometric analysis conducted with VOSviewer, encompassing publications from 2006 to 2025, reveals growing scholarly focus on SSCF, particularly in relation to fermentation, enzymatic hydrolysis, and lignocellulosic feedstocks. Notably, the complete absence of “bamboo shoot” as a keyword across the dataset signifies a critical research gap. This gap underscores the necessity for rigorous experimental investigations and the development of predictive simulation models employing bamboo shoots in SSCF, with the aim of optimizing ethanol yields, elucidating key process dynamics, and advancing sustainable bioethanol production. Keywords: bamboo shoot, bioethanol, simulation, simultaneous saccharification and co-fermentation (SSCF)